THE TEACHERS’ DIFFICULTIES IN ENGLISH INSTRUCTION AT MTS RAUDATUL ULUM - Siti Sofiyah (Universitas Madura, 2020)
The researcher investigates the specific problems as follows: (1) What are the teachers’ difficulties in English instruction at MTS Raudhatul Ulum? (2) How do the teachers overcome those difficulties in English instruction at MTS Raudhatul Ulum? This research use descriptive qualitative method because the researcher describe the teachers’ difficulties in English instruction and how the teachers overcome their difficulties. In collection the data the researcher use two kinds of data collection: observation and interview (interactive technique). Data source taken from the observation and interview. The interview were distributed to 2 English teachers of MTS Raudhatul Ulum. Teachers get three main difficulties that become a problem in English instruction. They were the difficulty on students’ mindset, difficulty on students’ interest toward English, and the last were the difficulty on students’ ability, the teachers difficult to instruct the students when they taught in the classroom. 2. There are three ways that the researcher found to overcoming those difficulties. The first is the teachers give spirit, the second is the teacher mix the language, using Indonesian language and both Indonesian and English language, but sometime the teacher using Arabic language, and the last is the teacher using innovative strategies when they taught in the classroom.